The impact of high-intensity interval training on anxiety: a scoping review - Wang, Yidan; Zhang, Xiaotu; Zhang, Ye; Zhang, Hongshi (Frontiers in Psychiatry, 2025)
BackgroundIn recent years, high-intensity interval training (HIIT) has gained significant attention due to its efficient use of time. Studies have shown that engaging in regular physical activity can effectively reduce symptoms of anxiety. Given the potential side effects and limitations associated with pharmacological treatments for anxiety disorders, there is a growing interest in exploring non-pharmacological interventions. HIIT, as an alternative approach, offers a promising avenue for managing anxiety without relying on medication. However, the specific efficacy and applicability of HIIT for individuals diagnosed with anxiety disorders have not been systematically summarized in the literature. This scoping review aims to explore the effectiveness of HIIT as an intervention for improving anxiety symptoms, as well as its range of applicability, by synthesizing existing research.MethodsA scoping review methodology was employed to search databases including PubMed, Web of Science, EMbase, and the Cochrane Library. Studies were selected based on predefined criteria: randomized controlled trials (RCTs), cohort studies, and quasi-experimental designs focusing on the improvement of anxiety, using HIIT as the primary intervention. Exclusion criteria included studies with mixed interventions or populations with comorbid conditions. Two independent evaluators screened titles, abstracts, and full texts, extracted data using a pre-tested form, and resolved discrepancies through discussion to ensure consistency and accuracy.ResultsA total of 541 articles were identified, of which 16 met the inclusion criteria for this review. The samples comprised various populations, including healthy subjects, overweight males, prostate cancer patients, etc. Twelve studies indicated that HIIT significantly improves anxiety symptoms, especially for individuals with lower baseline anxiety. The effect was less pronounced in those with higher baseline anxiety. Additionally, the studies suggest that variations in training protocols—such as frequency, intensity, and duration—may influence the extent to which HIIT improves anxiety symptoms.ConclusionsThis study underscores the potential of High-Intensity Interval Training (HIIT) as an effective intervention for reducing anxiety symptoms, especially when tailored to individual baseline characteristics. Variations in training parameters such as frequency, intensity, and duration are critical factors in optimizing HIIT’s effectiveness for mental health benefits.HIIT shows promise as a valuable tool for managing anxiety, with the potential to significantly improve mental health outcomes when implemented with careful consideration of individual differences and protocol variations. This study provides a foundation for refining HIIT protocols and expanding their applicability across diverse populations.